2015
DOI: 10.1038/srep13189
|View full text |Cite
|
Sign up to set email alerts
|

Association of p21 3′ UTR gene polymorphism with cancer risk: Evidence from a meta-analysis

Abstract: Numerous studies have investigated the risk of cancer associated with the polymorphism of p21 3′ UTR (rs1059234 C > T), but results have been inconsistent. We performed this meta-analysis to drive a more precise estimation of the association between this polymorphism and risk of cancer. A comprehensive search was conducted to identify all case-control studies of the rs1059234 C > T polymorphism of p21 3′ UTR and cancer susceptibility. A total of eleven eligible studies, including 3,099 cases and 4,354 controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…To the best of our knowledge, there is no study to examine the association between P21 variants and thyroid carcinoma. However, the possible role of the P21 polymorphisms and some cancers has been found previously . Two common polymorphisms of P21 , rs1801270 and rs1059234, were selected for this study.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, there is no study to examine the association between P21 variants and thyroid carcinoma. However, the possible role of the P21 polymorphisms and some cancers has been found previously . Two common polymorphisms of P21 , rs1801270 and rs1059234, were selected for this study.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that C > A substitution in rs1059234 at codon 31 of the P21 protein (nonsynonymous serine‐to‐arginine substitution, p.Ser31Arg) alters DNA binding of zinc finger motif and expression of P21 . Also, the rs1059234 polymorphism, in the 3'untranslated region of P21 affects mRNA stability and alters the level of protein expression and is implicated in the proliferation, differentiation, and tumor inhibition …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…miRNAs’ target site polymorphisms may potentially play a role in the interaction between miRNAs and their target mRNA, which is dependent on the effect of polymorphism on miRNA:mRNA interactions. There was also a meta‐analysis on 3'UTR polymorphisms and the risk of cancers, but the results were only for two polymorphisms and were not specific for CRC or miRNA‐binding sites. To the best of our knowledge, there is no previous systematic review on the association between miRNA‐binding site polymorphisms and CRC.…”
Section: Introductionmentioning
confidence: 99%